2015
DOI: 10.1515/hepo-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Cardinal temperatures for germination of Salvia leriifolia Benth

Abstract: Summary The focus of this study is based on the examination of the germination traits and the development of thermal models of the medicinal plant Salvia leriifolia Benth. A laboratory experiment was carried out at constant temperatures ranging from 0 to 35°C, at 5°C intervals in a completely randomized design with eight replications. To describe the germination rate response to temperature, three regression models, namely Intersected-Lines (ISL), Quadratic Polynomial (QPN) and Five-Parameters Beta (FPB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
2
0
1
Order By: Relevance
“…Similar results have been reported for GP, MGT and GR m of most plant species [20,22,26,42,43]. Most reports showed that increased temperature up to optimum followed by increased GR but declined thereafter [35,44,45].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results have been reported for GP, MGT and GR m of most plant species [20,22,26,42,43]. Most reports showed that increased temperature up to optimum followed by increased GR but declined thereafter [35,44,45].…”
Section: Resultssupporting
confidence: 86%
“…Khalili et al [43] and Heidari [28] reported Beta model to be the best one for interpreting germination rate of savory (Satureja hortensis) and milk thistle (Silybum marianum L.). Beta function model have been used by Jame and Cutforth [30], Dashti et al [35] and Parmoon et al [62] as the best-fitting output for cardinal temperatures, by its higher R 2 and lower RMSE. Tabrizi et al [34] also reported that FPB and ISL were the best fitted models for cultivated and natural stand seeds of Thymus transcaspicus.…”
Section: Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…A partir de los datos de germinación, por medio de métodos analíticos, se elaboraron los siguientes índices de germinación: Tasa de germinación [4] (TG) durante el periodo para cada tratamiento, según la siguiente ecuación (Dashti et al 2015), [4] Donde TG: tasa de germinación, n i : número de semillas recién germinadas en el momento t i , t i : tiempo (días) desde el inicio de la observación de la prueba de germinación y K: último día del experimento. Velocidad de germinación [5] (González-Zertuche y Orozco-Segovia 1996).…”
Section: Métodosunclassified
“…reached the highest final germination at 25 • C, compared with 4 • C and 10 • C [50], while Noroozak (Salvia leriifolia Benth.) has an optimal range between 15 and 25 • C, with a calculated Tb, To, and Tc of 1.00 • C, 19.0 • C, and 36.5 • C, respectively [51]. On the other hand, in an analysis conducted on 11 different medicinal plants [52], including two belonging to the Salvia genus, it was observed that Salvia sclarea L. and Salvia nemorosa L. reached the highest final germination and GR in the treatments at 20 The GR observed in our analysis was 1.4-fold and 2.2-fold higher than the one previously reported by Nadtochii et al [53] for 25 • C, and 30 • C (13.1 ± 0.1 and 9.7 ± 0.1), while at 20 • C, the GR was similar between the works (12.6 ± 0.1 and 12.75 ± 0.72, respectively).…”
Section: Germinationmentioning
confidence: 99%